Implementation of The Merdeka Curriculum in The Dance Learning of Smp Negeri 4 Demak (Universitas Negeri Semarang, 2022)
The curriculum in Indonesia has undergone changes and improvements, it is the Merdeka curriculum. The Merdeka Curriculum focuses on freedom and creative thinking. In the Merdeka Curriculum on the material learning the Arts of Dance, students are not only formed to be intelligent. The purpose of this research is to analyze the implementation of the Merdeka curriculum in dance learning for SMP Negeri 4 students Demak. The Data collection techniques used observation techniques, interviews, and documentation. Technique the validity of the data used the credibility test, transferability test, dependability test, and confirmability test. This type of research is descriptive qualitative research. The result of the research showed that implementation of the Merdeka Curriculum in Dance Learning for Students of SMP Negeri 4 Demak are the implementation of Merdeka curriculum based on the phases the achievements, it’s namely in phase D. The learning steps can be started from the initial activities, core activities, and activities closing. In learning the art of dance students are invited to take advantage of the state of the school environment as dance motion exploration material, with the hope that students can get to know the environment better, and it can influence others to create art.